Petrology of spinel lherzolite xenoliths and host basaltic lava from Ngao Voglar volcano, Adamawa Massif (Cameroon Volcanic Line, West Africa): equilibrium conditions and mantle characteristics - Nkouandou,O.F.; Temdjim,R. (Journal of Geosciences, 2011)
Spinel-bearing lherzolite xenoliths have been recovered from Mio-Pliocene alkaline basalt flows from the Ngao Voglar volcano, 35 km northwest of Ngaoundere in the Adamawa volcanic Massif (Cameroon). They have been examined to characterize the petrography, mineralogical composition, and equilibrium conditions of the upper mantle beneath the Ngaoundere region. The xenoliths exhibit protogranular textures and consist of four main minerals: olivine (Fo89-90); Mg-enstatite (En89-91Wo1Fs8-10), Cr-diopside (En49-52Wo44-49Fs1.5-5) and spinel (Mg# ˜79.2, Cr# ˜10.7).Thermobarometric calculations show equilibrium temperatures ranging between 850 and 950 °C and pressures of 8 to 17 kbar consistent with the spinel lherzolite stability field. These data suggest that the xenoliths come from a depth of 28-31km in the uppermost mantle situated just below a thinned crust; they are in agreement with the geophysical data previously determined in the Adamawa Massif. On the basis of these features, and considering the evidence for textural, mineralogical, and chemical equilibrium in the studied xenoliths prior to their entrainment in the host magma, we conclude that the source of these xenoliths was a chemically and petrographically homogeneous, spinel lherzolite lithospheric mantle. But the occurrence of mantle-derived xenoliths of various types (dunite, lherzolite, wehrlite, harzburgite, websterite, clinopyroxenite, and orthopyroxenite) in alkali basalts from many other localities of Cameroon (Oku Massif, Lake Nyos area and Mount Cameroon) is consistent with upper-mantle heterogeneities on a regional scale and implies that the nature of the upper mantle beneath the continental sector of the Cameroon Volcanic Line varies under its different volcanic centres.
Keywords: Cameroon Volcanic Line; Adamawa Massif; Ngaoundere region; Ngao Voglar volcano; lithospheric mantle; spinel-bearing lherzolite xenoliths